Leaf cutting propagating method of river pool primulina tabacum hance - CAI MING; LUO LE; ZHANG QIXIANG; WANG JIA; CHENG TANGREN; SUN MING; AI CHUNXIAO; PAN HUITANG (2013)
The invention discloses a leaf cutting propagating method of river pool primulina tabacum hance. The leaf cutting propagating method of the river pool primulina tabacum hance includes the following steps of (1) selecting cutting time, (2) preparing cutting slips, (3) preparing cutting bed, (4) cutting, (5) managing after cutting, (6) transplanting the river pool primulina tabacum hance into pots. By means of the leaf cutting propagating method of the river pool primulina tabacum hance, rapid propagation of the river pool primulina tabacum hance is achieved, seedlings are rounding and normal in plant type, little difference between the seedlings and stock plants exists, and the quality of seedlings is good and identical. In addition, by means of the leaf cutting propagating method of the river pool primulina tabacum hance, annual production of the river pool primulina tabacum hance can be achieved, possibility is provided for commercial production of the river pool primulina tabacum hance and the cost of the c